Effects of sexual assault vs. other traumatic experiences on emotional and cannabis use outcomes in regular cannabis users with trauma histories: moderation by gender? - Stewart, Sherry H.; Khoury, Juliana M. B.; Watt, Margo C.; Collins, Pamela; DeGrace, Sarah; Romero-Sanchiz, Pablo (Frontiers in Psychology, 2024)
Introduction: While sexual assault may have particularly adverse emotional effects compared with other forms of trauma, it remains unclear which emotional outcome dimensions are impacted, whether cannabis outcomes are similarly impacted, and whether gender differences exist in sexual assault’s links with these outcomes. Method: N=100 cannabis users with trauma histories (M age=33.1) completed standardized measures of demographics, trauma exposure, posttraumatic stress (PTS) and depressive symptoms, hopelessness, and cannabis outcomes (frequency, medicinal prescription, motives, and craving). Results: Sexual assault was experienced more often by women (83.9%) than men (31.8%). A series of 2 x 2 analyses of variance (gender: women [n=56] vs. men [n=44] x trauma type: sexual assault [n=61] vs. other [n=39]) and logistic regression revealed that sexual assault survivors scored higher than other trauma survivors on re-experiencing and hyperarousal PTS symptoms (DSM-5 Clusters B and E), cognitive depressive symptoms, hopelessness, cannabis use frequency, medicinal cannabis prescription, cannabis use to cope with psychological symptoms, and compulsivity craving; and lower on social and enhancement cannabis use motives. In terms of gender main effects, women scored higher than men on cannabis use to cope with negative emotions. In terms of interactions: for PTS Cluster D symptoms (negative alterations in mood/cognitions), among men only, sexual assault survivors scored higher than other trauma survivors; and for cannabis enhancement motives and purposefulness cannabis craving, among sexual assault survivors only, women scored higher than men. Discussion: Across many different trauma, women survivors’ use of cannabis to cope with negative affect should be a specific therapeutic focus. Moreover, we identified specific emotional and cannabis use outcomes that should be of specific clinical concern among sexual assault survivors regardless of gender. Finally, in terms of gender differences of clinical interest among sexual assault survivors, while PTS Cluster D symptoms should be specific treatment targets in men, cannabis enhancement motives and purposefulness craving should be treatment targets in women.